2010
DOI: 10.1073/pnas.0909862107
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ST6GalNAcV, a ganglioside-specific α2,6-sialyltransferase, inhibits glioma growth in vivo

Abstract: Aberrant cell-surface glycosylation patterns are present on virtually all tumors and have been linked to tumor progression, metastasis, and invasivity. We have shown that expressing a normally quiescent, glycoprotein-specific α2,6-sialyltransferase (ST6Gal1) gene in gliomas inhibited invasivity in vitro and tumor formation in vivo. To identify other glycogene targets with therapeutic potential, we created a focused 45-mer oligonucleotide microarray platform representing all of the cloned human glycotranscripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…The same concerns the influence of on cellular motility and invasive capabilities. For particular cell types overexpression of a-2,6-GalSA or a-2,6-ST enzyme has been associated with enhanced tumor migration potential (breast cancer cell line [22], colon cancer cell lines [23], HCC cell line [24]), whereas for other cell types this phenomenon results in impaired departure from the originating tissue (lymphosarcoma cell line MDAY-D2 [25]) and inhibition of tumor growth in vivo (glioma [26]). …”
Section: Discussionmentioning
confidence: 99%
“…The same concerns the influence of on cellular motility and invasive capabilities. For particular cell types overexpression of a-2,6-GalSA or a-2,6-ST enzyme has been associated with enhanced tumor migration potential (breast cancer cell line [22], colon cancer cell lines [23], HCC cell line [24]), whereas for other cell types this phenomenon results in impaired departure from the originating tissue (lymphosarcoma cell line MDAY-D2 [25]) and inhibition of tumor growth in vivo (glioma [26]). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that alteration of the proteomic profile of cancer and stromal cell populations between attractor and non-attractor GSC xenografts may provide insights into key biochemical pathways involved in the attraction of BM-hMSCs to gliomas. We have previously performed label-free quantitative proteomic and targeted transcriptomic studies on GSCs and GBM cells [23][24][25][26]. For the first time, we extend these methodologies to attractor and non-attractor GSCXs.…”
Section: Introductionmentioning
confidence: 99%
“…16.7 ) (Ma et al 2009(Ma et al , 2011Kessler et al 2007b ) . The glyco-related gene DNA-microarrays (Kroes et al 2011 ) , containing more than 300 different genes, also suggested (Tables 16.3 and 16.4 ) modulation of the transcriptional regulation (many were stimulated) of several GLTs involved in the biosynthesis of neolactosylceramide containing cell-surface antigens in these apoptotic breast carcinoma cells. In the early apoptotic stages (2-6 h after l -PPMP treatment) in addition to the GlcT-1 gene, several genes (betaGalTs and betaGlcNAcTs) in the SA-Lea pathway were stimulated (Tables 16.3 and 16.4 ).…”
Section: Regulation Of Glycosphingolipid Biosynthetic Genes In Apoptomentioning
confidence: 95%